Implementing LiGa - literature and gamification: Usability and Effectiveness of Analog Gamification in Brazilian Elementary Education - Prado, Victor H. do; Marinho, Élton Carneiro; Delgado, Carla Amor Divino Moreira; Silva, Mônica Ferreira da (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
This paper investigates LiGa - Literature and gamification, an analog educational strategy aimed at modernizing literature education for public elementary schools in Brazil. It was developed considering Brazil's disparities in digital access and public education challenges. LiGa integrates gamification concepts into printed didactic materials. The study assesses LiGa's usability and effectiveness through teachers perceptions, within the public education network of Itararé-SP, where it was first implemented. For this study, it was primarily used the System Usability Scale (SUS). Findings indicate good usability, in face of specific considerations and limitations of this implementation and research.